Homo erectus adapted to steppe-desert climate extremes one million years ago - Julio Mercader; Pamela Akuku; Nicole Boivin; Alfredo Camacho; Tristan Carter; Siobhán Clarke; Arturo Cueva Temprana; Julien Favreau; Jennifer Galloway; Raquel Hernando; Haiping Huang; Stephen Hubbard; et al. (Communications Earth & Environment)
Abstract Questions about when early members of the genus Homo adapted to extreme environments like deserts and rainforests have traditionally focused on Homo sapiens. Here, we present multidisciplinary evidence from Engaji Nanyori in Tanzania’s Oldupai Gorge, revealing that Homo erectus thrived in hyperarid landscapes one million years ago. Using biogeochemical analyses, precise chronometric dating, palaeoclimate simulations, biome modeling, fire history reconstructions, palaeobotanical studies, faunal assemblages, and archeological evidence, we reconstruct an environment dominated by semidesert shrubland. Despite these challenges, Homo erectus repeatedly occupied fluvial landscapes, leveraging water sources and ecological focal points to mitigate risk. These findings suggest archaic humans possessed an ecological flexibility previously attributed only to later hominins. This adaptability likely facilitated the expansion of Homo erectus into the arid regions of Africa and Eurasia, redefining their role as ecological generalists thriving in some of the most challenging landscapes of the Middle Pleistocene.